Pengaruh Komite Audit, Corporate governance, dan Audit Tenure Terhadap Integritas Laporan Keuangan pada Perusahaan Sektor Energi - Suci Tania; Emilia Gustini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of the Audit Committee, Corporate Governance, and Audit Tenure on the integrity of financial reports in energy sector companies listed on the Indonesia Stock Exchange for the 2021–2023 period. The issue of financial reporting integrity has come under scrutiny due to numerous cases of manipulation and weak transparency in the energy sector. Using a quantitative approach and multiple linear regression analysis on 105 observational data sets, this study simultaneously and partially examines the influence of independent variables on financial report integrity, as proxied by earnings management. The results indicate that the Audit Committee and Audit Tenure have a significant positive effect on financial report integrity, with significance values of 0.017 and 0.002, respectively. Conversely, Corporate Governance has no significant effect (sig = 0.141), although the relationship is positive. These findings emphasize the importance of effective audit oversight and a stable auditor-client relationship in maintaining the reliability of financial reports, while the implementation of Corporate Governance needs to be substantially strengthened. This research contributes to understanding the determinants of financial reporting quality in strategic, risk-prone sectors.